2017
DOI: 10.1590/0103-8478cr20160928
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance of soybean cultivars grown in different plant densities

Abstract: Plants density in soybean cultivation is an important management practice to achieve high grain yield. In this way, the objective was to evaluate the agronomic traits and grain yield in soybean in different plant densities, in two locations in the south of Minas Gerais. The experimental design was in randomized blocks, arranged in a split plot design, with three replications. Plots were composed of four population densities (300, 400, 500 and 600 thousand plants per hectare) and the subplots were composed of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
4
16
0
1
Order By: Relevance
“…The insertion height of the first pod showed within the studied interval a linear increase as a function of increasing sowing density (Figure 3, A). It is a result that corroborates with those found by Mauad, Silva, Almeida-Neto and Abreu (2010) and Ribeiro et al (2017) in which they reported that for the insertion height of the first pod, it could be observed that the increase in the number of plants per hectare provides an increase in the insertion height.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The insertion height of the first pod showed within the studied interval a linear increase as a function of increasing sowing density (Figure 3, A). It is a result that corroborates with those found by Mauad, Silva, Almeida-Neto and Abreu (2010) and Ribeiro et al (2017) in which they reported that for the insertion height of the first pod, it could be observed that the increase in the number of plants per hectare provides an increase in the insertion height.…”
Section: Resultssupporting
confidence: 91%
“…In research conducted and evaluated in the state of Minas Gerais, similar results regarding the nonsignificant effect for interaction cultivars vs densities were reported by Bisinella and Simonetti (2017) for the parameters root and aerial part length and by Ribeiro et al (2017) for plant height, number of pods, number of grains and number of grains per pod when studying the productive performance of soybean grown at different densities. As well as the present work, Ribeiro et al (2017) selected soybean cultivars with similarity in maturity timing (similar maturity group among the assessed cultivars) and growth habit (indeterminate). Moreover, they reported the need to conduct and evaluate tests in different locations to measure the effects of cultivation sites.…”
Section: Resultssupporting
confidence: 76%
“…Another hypothesis is that the greater accumulation of photoassimilates leads to greater fruiting [34]. The number of grains per pod is a characteristic with high uniformity and is not impacted by EDAS (Table 5), since it does not respond to intraspecific competition [35]. The absence of significant variations in the number of grains per pod implies that the number of grains per plant only corroborates the differences caused by the EDAS in the number of pods per plant.…”
Section: Discussionmentioning
confidence: 97%
“…It is noted that, except for plot number 8, every plot aforementioned is in the group with the introduction of 15 plants m -1 . This finding may be explained by the 2015/2016 harvest based on the report published by RIBEIRO et al (2017) which stated that in low densities soybean plants tend to produce more branches and; therefore, increase the number of pods per plant and the number of grains by pod as well. As a result, there are fewer plants per area and increased production by each individual.…”
Section: Achieved Productivitymentioning
confidence: 99%